2015
DOI: 10.1111/cfs.12243
|View full text |Cite
|
Sign up to set email alerts
|

Child welfare clients and educational transitions

Abstract: A B S T R AC TDespite long-standing knowledge about child welfare clients' educational disadvantage, we know less about the individuals' progress through the educational system. Based on Norwegian data, this study examined educational transitions following compulsory school and the first 3 years of upper secondary school, which correspond approximately to the transition following middle school/junior high school to the first years of high school in the USA. It is argued that in examining educational success in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
5
0
4
Order By: Relevance
“…Six papers used an intervention design (e.g., Carmen, Waycott & Smith, ), four used a comparison design (e.g., Dæhlen, ), two used a quasi‐experimental design (e.g., Mandy, Murin, Baykaner, Staunton, Hellriegle, Anderson & Skuse, ) and one used a randomised control trial (Farmer et al , ). Some studies reported on qualitative designs, including phenomenological (n = 1), ethnographic (n = 2) and case study (n = 5) designs.…”
Section: Resultsmentioning
confidence: 99%
“…Six papers used an intervention design (e.g., Carmen, Waycott & Smith, ), four used a comparison design (e.g., Dæhlen, ), two used a quasi‐experimental design (e.g., Mandy, Murin, Baykaner, Staunton, Hellriegle, Anderson & Skuse, ) and one used a randomised control trial (Farmer et al , ). Some studies reported on qualitative designs, including phenomenological (n = 1), ethnographic (n = 2) and case study (n = 5) designs.…”
Section: Resultsmentioning
confidence: 99%
“…Future studies should aim at explaining the remaining part of the association by considering other indicators of disadvantage, measured from adolescence and onwards, such as behavioural problems, poor housing, somatic ill-health, low general well-being, early childbearing and family disruption, and poor educational attainment. In particular, past research has identified educational failure as a fundamental explanation for the adverse long-term outcomes of child welfare clients [9, 2123].…”
Section: Discussionmentioning
confidence: 99%
“…In general, about 97 per cent of the students in a given cohort enrol directly into upper secondary school (Statistics Norway, 2014). In the child welfare population, 89 per cent of the students in a given cohort proceed directly from compulsory school to upper secondary school (Daehlen, 2015a).…”
Section: The Norwegian Contextmentioning
confidence: 99%